Pengaruh Atraksi dan Aksesibilitas Terhadap Tingkat Kunjungan Wisatawan di Kebun Binatang Surabaya - Rahmatin, Leily Suci; Jamil, Nur Asyiah; Ardhana, Awara Aleyda; Faudi, Adinda Novaliza (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
Surabaya Zoo is a popular tourist attraction for different people both in Surabaya city and around East Java. Surabaya Zoo pursues the concept of recreational and educational tourism with a total of about 3,500 species of animals. The purpose of this study was to determine the impact of attractiveness and tourist accessibility on the number of tourist visits to Surabaya Zoo. The research method used is a quantitative approach with correlation research. Using a targeted sampling method, her 50 respondents of working age had visited Surabaya Zoo. The results show that different attractions and accessibility influence tourist visit levels by 59.7%. However, the attraction variable has a greater and significant influence on the level of tourist visits with a value of 0.626. Meanwhile, the accessibility variable has no significant effect on the level of tourist visits with a value of 0.190.